The impacts of bed rest and acute trauma on muscle metabolic health in humans - Shur, Natalie F. (2024)
Physical inactivity is a global public health problem and has significant detrimental health consequences. Periods of physical inactivity or immobilisation are common in clinical populations secondary to injury, illness, disease or advancing age. There are currently substantial gaps in our knowledge of the rate and magnitude of skeletal muscle and metabolic dysregulation during bed rest and trauma. Further insight into the processes underpinning these changes is required to develop effective future countermeasures.